Implementation of basic life support education for the lay public in China: barriers, enablers, and possible solutions - Xuejie Dong; Lin Zhang; Zongbin Wang; Zhi-jie Zheng (Frontiers Media S.A., 2024)
BackgroundEducation for the lay public in basic life support (BLS) is critical for increasing bystander cardiopulmonary resuscitation (CPR) rates and improving survival from out-of-hospital cardiac arrest (OHCA). Despite years of implementation, the BLS training rate in China has remained modest. The aim of this study was to investigate the factors influencing the implementation of BLS training programs in emergency medical service (EMS) centers in China and to identify specific barriers and enablers.MethodsQualitative interviews were conducted with key informants from 40 EMS centers in Chinese cities. The participants included 11 directors/deputy directors, 24 training department leaders, and 5 senior trainers. The interview guide was based on the Exploration, Preparation, Implementation, Sustainment (EPIS) framework. Thematic content analysis was used to identify themes and patterns across the interviews.ResultsWe identified 16 factors influencing the implementation of BLS training programs encompassing the outer content, inner context, innovation and bridging factors. Some factors acted as either barriers or enablers at different EPIS stages. The main implementation barriers included limited external leadership, insufficient government investment, low public awareness, a shortage of trainers, an absence of incentives, an absence of authoritative courses and guidelines, a lack of qualification to issue certificates, limited academic involvement, and insufficient publicity. The main enablers were found to be supportive government leaders, strong public demand, adequate resources, program champions, available high-quality courses of high fitness within the local context, the involvement of diverse institutions, and effective publicity and promotion.ConclusionOur findings emphasize the diversity of stakeholders, the complexity of implementation, and the need for localization and co-construction when conducting BLS training for lay public in city EMS centers. Improvements can be made at the national level, city level, and EMS institutional level to boost priority and awareness, promote legislation and policies, raise sustainable resources, and enhance the technology of BLS courses.